Adiwiyata as an Instrument of Social Transformation in Environmental Education: Literature Analysis of Concept, Implementation, and Challenges - Notrilauvia, Nindy; Marhamah, Ithvi; Nanda, Rama (JPASDEV : Journal of Public Administration and Sociology of Development, 2025)
Adiwiyata program is one of the strategic policies of the Indonesian government in an effort to mainstream environmental education at the educational unit level. More than just an environmentally friendly school award program, Adiwiyata acts as an instrument of social transformation that encourages changes in culture, values, and behavior of school residents towards the environment collectively and sustainably. This article aims to examine the basic concept, implementation, and challenges of the Adiwiyata program through a systematic literature review approach to various scientific journals, policy documents, and research reports. The results of the study indicate that Adiwiyata is able to encourage active participation of school residents, form environmentally conscious characters, and integrate sustainability values into educational governance. However, the challenges faced include weak internalization of values, dependence on school leadership, limited budget support, and formal orientation for awards. Thus, the Adiwiyata program needs to be viewed as part of an education-based social change strategy, not merely as a technocratic program. Strengthening institutional capacity, community participation, and continuous evaluation are the keys to the success of the expected transformation.Keywords: Adiwiyata, social transformation, environmental education, green schools